Public Libraries and Internet Access across the United States: A Comparison by State 2004–2006 - Jaeger, Paul T.; Bertot, John Carlo; McClure, Charles R.; Rodriguez, Miranda (Information Technology and Libraries, 2007)
Drawing upon findings from a national survey of U.S. public libraries, this paper examines trends in Internet and public computing access in public libraries across states from 2004 to 2006. Based on library-supplied information about levels and types of Internet and public computing access, the authors offer insights into the network-based content and services that public libraries provide. Examining data from 2004 to 2006 reveals trends and accomplishments in certain states and geographic regions. This paper details and discusses the data, identifies and analyzes issues related to Internet access, and suggests areas for future research.